Cardiovascular risk factors and modern therapeutic strategies in children and adolescents with type 1 diabetes to prevent future diabetic angiopathy in the era of innovative miRNAs biomarkers - Peczyńska, Joanna; Odyjewska, Emilia; Koszykowska, Kamila; Jamiołkowska-Sztabkowska, Milena; Bossowski, Artur; Głowińska-Olszewska, Barbara (Frontiers in Endocrinology, 2025)
Type 1 diabetes (T1D) in children is a serious, chronic, incurable disease associated with the frequent and early occurrence of additional, well-known cardiovascular risk factors and exacerbation of the risk of future cardiovascular diseases (CVD). Lately, accumulating evidence suggests that exosomal miRNAs play a major role not only in the pathophysiology of T1D but also in its late complications. Since premature CVD is one of the leading causes of morbidity and mortality in diabetes, considerable efforts have been made to define the molecular and pathological features and to develop new diagnostic and therapeutic strategies. Dysregulation of the expression or function of various miRNAs may affect angiogenesis, vascular inflammation, or cardiac remodeling, which play key roles in the development and progression of cardiovascular complications. While CVD usually appear in adulthood, pathology and early markers may appear during adolescence, emphasizing the need for careful monitoring and prevention in this age group. In this narrative review, we aimed to summarize the latest findings on miRNAs and their role as biomarkers of cardiovascular risk factors and subsequent complications in children with T1D, presenting promising candidates for clinical applications.